The Role of Tissue Engineering in Orthodontic and Orthognathic Treatment: A Narrative Review - Rosana Farjaminejad; Samira Farjaminejad; Melika Hasani; Franklin Garcia-Godoy; Babak Sayahpour; Anand Marya; Abdolreza Jamilian (Oral)
Background: Orthodontics and orthognathic surgery present challenges such as extended treatment durations, patient discomfort, and complications like root resorption. Recent advancements in tissue engineering and nanotechnology offer promising solutions by improving bone regeneration, periodontal repair, and biomaterial integration. Objectives: This review explores the integration of scaffold-based tissue engineering and nanotechnology in orthodontics, focusing on their roles in accelerating bone regeneration, reducing treatment times, and minimizing adverse effects to enhance the predictability and success of orthodontic interventions. Methods: Relevant literature was selected from PubMed, Scopus, and Web of Science, focusing on studies related to scaffold technology, biomaterials, and nanotechnology in orthodontics. Keywords included “tissue engineering”, “orthodontics”, “biomaterials”, “scaffolds”, “nanotechnology”, and “bone regeneration”. Priority was given to peer-reviewed original studies, systematic reviews, and meta-analyses addressing innovative treatment approaches and clinical outcomes. Results: Findings indicate that scaffolds enhance bone regeneration and periodontal repair, while nanoparticles improve biomaterial integration and drug delivery efficiency. These advancements contribute to faster, more predictable orthodontic treatments with reduced complications. However, challenges such as high costs, regulatory hurdles, and the need for long-term clinical validation remain barriers to widespread adoption. Conclusions: Tissue engineering and nanotechnology offer minimally invasive, biologically driven solutions for orthodontic treatment. While significant progress has been made, further clinical studies, cost-effective strategies, and regulatory approvals are needed to integrate these innovations into routine practice.